Keragaman Perilaku Petani Padi Dalam Penjualan Gabah (Kasus Di Kecamatan Air Manjunto, Kabupaten Mukomuko, Provinsi Bengkulu) - Andi Ishak; Jhon Firison; Rokhani Rokhani (UPT Penerbitan Universitas Jember, 2018)
Rice farming in irrigated land has a dual purpose, namely to fulfill the family's riceneeds and obtain income from the sale of production surplus. The aim of this study was todetermine the diversity of farmer's behavior in selling grain and the factors that influence it. Thestudy was conducted in two villages namely Tirta Makmur and Tirta Mulya Villages in AirManjunto District Mukomuko Regency in April to May 2017. Data was collected through indepthinterviewswith14farmergroupleadersasinformantsregardingthebehaviorofricepaddy farmers selling grain and reasons the background. Data analysis was carried out descriptivelyusing an interactive model. The results showed that there were three patterns of farmers' behaviorin selling grain, namely direct selling of harvested dry grain (GKP) carried out by around 60% offarmers, delayed selling by 30% of farmers, and borrowing selling by 10% of farmers. The patternof sales by delay selling results in the highest revenue of Rp. 29,150,000/ha, compared to directselling (Rp. 25,200,000/ha) and borrowing selling (Rp. 26,400,000). Factors that influence thediversity of farmers' behavior patterns in selling grain are grain prices at harvest, economicconditions of farmer households, and farmer relations with rice trader collectors that determinesthe bargaining power of farmers.